The problematic character in the Iraqi novel narrative My novels The Great Dream and The Death of the Father by Ahmed Khalaf are an example (Journal of the College of Basic Education, 2024)
The term problematic hero is a definitional model for the anxious fictional character who is ideologically and psychologically unstable, who is often the product of the known conflict caused by his society, or who is experiencing a stage of controlling the sovereignty of this society. From Lukács’ point of view, this hero is neither negative nor positive at all. He is a hero who lives in a struggle between the world of the self and reality, and refuses to be in conflict with reality, as the hero has authentic values ​​that he fails to establish in a world, and he lives in a stage of intellectual and moral decadence, dominated by market concepts and values. ,Main vocabulary: the Iraqi novel, Ahmed Khalaf, the novel The Great Dream, the novel (Death of the Father).